Beveling of quartz crystal blanks: an experimental study - Dong, Chensong (Taylor and Francis, 2012)
An experimental study on the beveling of quartz crystal blanks is presented in this paper. Two issues in the beveling are addressed: beveling time and the shape of bevel. The time needed for beveling is determined by material removal rate. The concept of critical gap height is introduced to evaluate the bevel profile. In addition, a side effect, frequency shift is also studied. Seven potential relevant process factors: blank quantity, powder/blank ratio, powder type, machine rpm, powder changing time, barrel diameter and powder heating were identified. The influences of these process factors on material removal rate, critical gap height and frequency shift were studied using Design of Experiments (DOE). It is shown from the results that (1) machine rpm has the most significant effect on material removal rate, followed by barrel diameter. Material removal rate increases with machine rpm and barrel diameter; (2) steeper bevel profiles can be achieved by using barrels of smaller diameter and finer powders; and (3) machine rpm has the most significant effect on the frequency shift, followed by barrel diameter and powder type. The frequency shift increases with the machine rpm and barrel diameter. Using finer powders can reduce the frequency shift.